Coupled Investigation of Contact Potential and Microstructure Evolution of Ultra-Thin AlOx for Crystalline Si Passivation - Zhen Zheng; Junyang An; Ruiling Gong; Yuheng Zeng; Jichun Ye; Linwei Yu; Ileana Florea; Pere Roca i Cabarrocas; Wanghua Chen (Nanomaterials, 2021)
In this work, we report the same trends for the contact potential difference measured by Kelvin probe force microscopy and the effective carrier lifetime on crystalline silicon (c-Si) wafers passivated by AlOx layers of different thicknesses and submitted to annealing under various conditions. The changes in contact potential difference values and in the effective carrier lifetimes of the wafers are discussed in view of structural changes of the c-Si/SiO2/AlOx interface thanks to high resolution transmission electron microscopy. Indeed, we observed the presence of a crystalline silicon oxide interfacial layer in as-deposited (200 °C) AlOx, and a phase transformation from crystalline to amorphous silicon oxide when they were annealed in vacuum at 300 °C.